The regulatory VirG protein specifically binds to a cis-acting regulatory sequence involved in transcriptional activation of Agrobacterium tumefaciens virulence genes. - Jin, S G (1990)
Virulence genes of Agrobacterium tumefaciens are induced in parallel in the presence of plant phenolic compounds such as acetosyringone and the two regulatory vir genes virA and virG. In this study we identified a cis-acting regulatory sequence in the 5'-noncoding region of the virE operon that is essential for this activation. To do this, we constructed a series of deletion mutants by using exonuclease Bal 31. Western blot (immunoblot) analysis showed that the 70 base pairs upstream of the transcriptional start site were sufficient for full virE gene induction. A conserved dodecadeoxynucleotide sequence (vir box), which was previously identified in the nontranscribed sequences of all vir genes, was located at 5' end of the minimum required promoter sequence. Deletion of this vir box only completely abolished induction of the virE gene. This demonstrates that the vir box functions as an upstream regulatory sequence. To study the role of the VirG protein in the activation process, we overproduced the native-sized VirG protein in Escherichia coli by fusing the lacZ' start codon ATG with the second virG codon AAA using site-directed mutagenesis. The VirG protein was purified and renatured from E. coli and was shown to bind to a specific sequence in two vir gene promoters. Footprinting analysis of the virE and virB promoters identified the 12-base-pair vir box as the VirG-binding core sequence.